THE DEVELOPMENT OF SCHOOLCHILDREN TECHNICAL EDUCATION IN THE TRANSITION TO A NEW TECHNOLOGICAL PARADIGM - D. A. Mahotin (Russian State Vocational Pedagogical University, 2017)
Introduction. The transition to a new technological regime leads to social-economic and technological changes that require representation not only in the sphere of professional education but also in general school education. Processes of modernization of the content and curriculum of general education particularly acute become applicable in the subject area "Technology", which is the basis for formation of technological culture of the graduates and successful development of their professional education.The aim of the publication is to justify the need for changes in the content and means of technological education in connection with the transition of society to a new technological structure, changing nature of work and basic production techniques.Methodology and research methods. The methodological basis of the study was the concept of substitution of technological regime and the concept of change of organizational cultures that determine the regularities of changes in the means and nature of work in society. The research methods involve the analysis of the current state of the system of technological education; problem statement and conceptualization; expert survey, generalization.Results and scientific novelty. The necessity of the content and means of technological education is proved. The mentioned above necessity defines the quality of future vocational training of students according to the changing requirements of labour market, the last achievements in the technical field and technologies; serves as a warranty of maintaining competitiveness of national economy in global scales of social-economic and technological development of world production. The common regularities of changes in technological education under the influence of change of technological regimes (industrial revolutions) are described. The essence of the contents and means of technological education is disclosed. The measures of such training implementation are proposed.Practical significance. The article can be used by researchers of technological education of students; authors of new approaches and modernization concept development of technological education content.